Making of a smart city - Goel, S. L.; Rajneesh, Shalini (Bengaluru Sapna Books House, 2018)
The book is like a "one stop shop" for all Stakeholders who are involved in Urban governance in general and making of a smart city , in particular. The increasing pace of urbanization and its role in spurring economic growth ,necessitates efficient and effective urban planning, monitoring and evaluation. In this process people's participation is of utmost importance, which can eventually lead to higher index of happiness and prosperity of the people. The smart cities are the need of the hour. Smart cities have vast potential to improve quality of life of citizens, provided the capacity of functionaries is built along with autonomy and responsibility. The authors' inputs based on vast experience in public administration, can help enhance the success and sustainability of upcoming Smart cities.
Keywords: Smart city; IAS as a second author